2023
DOI: 10.3390/ijtm3010005
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in the Diagnosis of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common primary liver malignancy, with increasing global incidence. Morbidity and mortality associated with HCC remains high, and HCC is the leading cause of cancer death worldwide. Early detection and treatment of HCC can increase five-year survival by over 60%. Detection of HCC remains challenging, however, as HCC arises from a variety of environmental, genetic, and viral etiologies, and it demonstrates a complex pathophysiology and displays a heterogeneous morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…The current diagnostic tools for HCC include ultrasonography, CT, magnetic resonance imaging (MRI), and biopsy[ 39 ]. Biopsy confirmation is usually not required for a diagnosis[ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current diagnostic tools for HCC include ultrasonography, CT, magnetic resonance imaging (MRI), and biopsy[ 39 ]. Biopsy confirmation is usually not required for a diagnosis[ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We discuss the evolution of key concepts in the field as well as the major technologies, the development pipelines of cancer biomarkers with a particular focus on pancreatic and liver cancer biomarkers. Pancreatic and liver cancers are known as some of the cancer types remarkably difficult to detect early, with particularly high morbidity and mortality, so we put a special emphasis on examining the advancements on the early detection of these two types of malignancies. The objective of the paper is to provide a broad overview of the evolving landscape of current knowledge on cancer biomarkers, to outline challenges and evaluate growth opportunities, in order to further efforts to solve the problems that remain.…”
Section: Biomarker Research Growthmentioning
confidence: 99%
“…Combining tumor markers with ultrasound may improve HCC detection accuracy. A combination of ultrasound and DCP had higher sensitivity and specificity than ultrasound alone for detecting early HCC, according to a systematic review and meta-analysis [24,25]. Other studies have found that using a panel of three different HCC markers (AFP, DCP, and OPN) together had a higher sensitivity rate than using each marker alone [26][27][28].…”
Section: Serum Markersmentioning
confidence: 99%